Mechanical properties of kenaf core sandwich panel toughened with modified epoxy - Hassan, Noor Azlina; Hassan, Norita; Johari, Norhasnidawani; Halim, Zahurin; Ahmad, Zuraida (Trans Tech Publications, 2015)
Kenaf-core sandwich panels were prepared by hand lay-up method with the optimum characteristics. The aim of this study is to determine the effects of modified epoxy on the mechanical properties of the sandwich panel. Mechanical test such as flexural, drop impact and tensile test were performed to investigate the optimum system of kenaf-core sandwich panel within 0-5wt% of kenaf fiber content. It revealed that the optimum loading of kenaf fiber was at 3wt%. Furthermore, this system was studied with the incorporation of liquid natural rubber (LNR) as impact modifier. All tests have been carried out according to the ASTM 365, C297, C393, and D1736. Each final data point is an average value that has been obtained based on a statistical sampling of four specimens. The main element of core structure is kenaf and the skin used in this study is aluminium type 1100. According to compression, flatwise tensile, three point bending and drop impact tests, 3wt% of LNR content exhibit as an excellent impact modifier, in modifying the mechanical properties due to rubber toughening. In addition of too much liquid natural rubber more than 5wt% was substantially interrupted the system.